2012
DOI: 10.6002/ect.2012.0066
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pure Red-Cell Aplasia With Cyclosporine in a Renal Transplant Patient

Abstract: Acquired pure red-cell aplasia is a rare disorder that can be either idiopathic or associated with certain autoimmune diseases, pregnancy, lymphoproliferative disorders, nutritional deficiencies, or medicines. We present a deceased-donor renal transplant patient who developed pure red-cell aplasia associated with mycophenolate mofetil or tacrolimus and was treated with cyclosporine. A 20-year-old woman was transplanted from a deceased donor 1 month earlier and presented to us with symptoms of fatigue, prostrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Systemic corticosteroids are the drug of first choice, followed by immune modulating medications such as cyclosporine in those unable to achieve remission . Studies in renal transplant patients have shown that changing the immunosuppressant regimen can lead to improvement in anemia . IVIG also plays a role in treatment, typically in immune compromised patients with PRCA thought to be secondary to parvovirus B19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic corticosteroids are the drug of first choice, followed by immune modulating medications such as cyclosporine in those unable to achieve remission . Studies in renal transplant patients have shown that changing the immunosuppressant regimen can lead to improvement in anemia . IVIG also plays a role in treatment, typically in immune compromised patients with PRCA thought to be secondary to parvovirus B19 …”
Section: Discussionmentioning
confidence: 99%
“…12 Studies in renal transplant patients have shown that changing the immunosuppressant regimen can lead to improvement in anemia. 13 IVIG also plays a role in treatment, typically in immune compromised patients with PRCA thought to be secondary to parvovirus B19. 12 Our patient had 2 plausible causes of the primary anemia that we could identify, the anti-M antibody and the possible effect of mycophenolate mofetil.…”
Section: A S E Rep Ortmentioning
confidence: 99%
“…Ancak nakil hastalarında immünsupresyon sonrasında saf eritrosit aplazisi bildirilmiştir ve nakil sonrasında mikofenolat mofetil ile ilişkili MDS bildirimi bulunmamaktadır. 15 Olgumuzda, siklosporin ve mikofenolat mofetil kesilerek sirolimus başlanmıştır. MDS tedavisinde sitotoksik ajanlar ve immünsup-resifler kullanılabildiği gibi destek tedavi ile de hastalar takip edilmektedir.…”
Section: Discussionunclassified